Train Once and Explain Everywhere: Pre-training Interpretable Graph Neural Networks - Yin, Jun; Wang, Senzhang; Yang, Hao; Li, Chaozhuo; Lian, Jianxun (NeurIPS 2023, 2023)
Intrinsic interpretable graph neural networks aim to provide transparent predictions by identifying the influential fraction of the input graph that guides the model prediction, i.e., the explanatory subgraph. However, current interpretable GNNs mostly are dataset-specific and hard to generalize to different graphs. A more generalizable GNN interpretation model which can effectively distill the universal structural patterns of different graphs is until-now unexplored. Motivated by the great success of recent pre-training techniques, we for the first time propose the Pre-training Interpretable Graph Neural Network (π-GNN) to distill the universal interpretability of GNNs by pre-training over synthetic graphs with ground-truth explanations. Specifically, we introduce a structural pattern learning module to extract diverse universal structure patterns and integrate them together to comprehensively represent the graphs of different types. Next, a hypergraph refining module is proposed to identify the explanatory subgraph by incorporating the universal structure patterns with local edge interactions. Finally, the task-specific predictor is cascaded with the pre-trained π-GNN model and fine-tuned over downstream tasks. Extensive experiments demonstrate that π-GNN significantly surpasses the leading interpretable GNN baselines with up to 9.98% interpretation improvement and 16.06% classification accuracy improvement. Meanwhile, π-GNN pre-trained on graph classification task also achieves the top-tier interpretation performance on node classification task, which further verifies its promising generalization performance among different downstream tasks. Our code and datasets are available at https://anonymous.4open.science/r/PI-GNN-F86C